13de Beretning. Forsøg paa Mejerivæsenets Omraade. Foredrag, den 28de Januar 1880. - Fjord, N. J. (Tidsskrift for Landøkonomi, 2018)
13de Beretning. Forsøg paa Mejerivæsenets Omraade. Foredrag, den 28de Januar 1880.